Caught in the Middle: How and When Psychological Contract Breach by Subordinates Relates to Weekly Emotional Exhaustion of Supervisors - de Jong, Jeroen P.; Clinton, Mike; Bal, Matthijs; Van Der Heijden, Beatrice (Frontiers in Psychology, 2021)
In psychological contract research, the side of the supervisor is strongly underexposed. However, supervisors are responsible for maintaining relationships with both their subordinates and senior management and are likely to be influenced by events unfolding in these relationships. In this study, we state that supervisor well-being may be affected by subordinates who fail to meet their obligations. This study adds to psychological contract research by developing an understanding of how and when subordinate psychological contract break (PCB) is associated with supervisor emotional exhaustion. Through a weekly diary survey among 56 Dutch supervisors, we test hypotheses about the relationships between subordinate PCB and the emotional exhaustion of the supervisor, the mediating role of perceptions of performance pressure by the supervisor in this relationship, and the moderating role of i-deals between the supervisor and senior management. Multilevel analyses support the first two hypotheses, but contradictory to our expectations show that the positive association between subordinate PCB and the emotional exhaustion of the supervisor is strengthened when the supervisor has high levels of i-deals with senior management. We discuss the findings in relation to their contribution to psychological contract theory.